ANALYSIS OF LOW SPEAKING AND LISTENING ABILITIES OF GRADE 4 ELEMENTARY SCHOOL STUDENTS IN ENGLISH LANGUAGELEARNING AT SD PAB 12 SAMPALI - Eva Betty Simanjuntak; Dea Yuanita Nasution; Claudia Simorangkir; Intan Arnianda; Khairunnisa; Nadila Dirawan Tanjung (Indonesian Journal of Elementary Education (IJETE), 2025)
This study aims to analyze the low English speaking and listening skills of 4th grade elementary school students at SD PAB 12 Sampali. The research approach used is descriptive qualitative, with interview methods to obtain in-depth data from teachers and students regarding the obstacles they face during the English learning process. The results of the study indicate that the main factors influencing students' limited speaking and listening skills include lack of practice, minimal use of interesting learning media, and internal factors such as lack of self-confidence and less than optimal pronunciation. These findings provide an important overview of the need to develop more effective and innovative learning strategies to improve students' communication skills in English at the elementary level. It is hoped that the results of this study can be a reference for educators and educational institutions in improving the quality of English teaching in elementary schools.